Human Resource Management Strategy in Early Childhood Education Institutions - Dian Hikmayana (SAHABAT: Jurnal Pendidikan Anak Usia Dini, 2025)
Human resource management plays a strategic role in determining the quality of management in Early Childhood Education (PAUD) institutions. Educators, as the frontline of educational services, need to be managed systematically to ensure the delivery of learning that aligns with the developmental characteristics of early childhood. This study aims to analyze human resource management strategies in PAUD institutions to improve the quality of learning and educational services. The research employed a qualitative approach using a library research design. Data were collected through a review of books, scholarly journal articles, and previous research relevant to human resource management and early childhood education. Data analysis was conducted using content analysis by categorizing findings based on human resource management strategy themes. The results indicate that human resource management strategies in PAUD institutions include human resource planning, recruitment and selection of educators, development and training, performance appraisal, as well as the provision of rewards and motivation. The integrated and sustainable implementation of these strategies can enhance educator professionalism, workforce stability, and the quality of PAUD learning.